Effects of different nutrient concentrations and reuse of substrate in tomato production - Marin, M. V. [UNESP]; Melo, D. M. [UNESP]; Gomes, R. F. [UNESP]; Diniz, G. M.M. [UNESP]; Rabelo, H. O. [UNESP]; Castoldi, R. [UNESP]; Gobato, E. D. [UNESP]; Azevedo, R. G. [UNESP]; Braz, L. T. [UNESP]; Fernandes, C. [UNESP] (International Society for Horticultural Science (ISHS), 2015)
Reusing the substrate in subsequent crops has been proposed due to several advantages, especially economic and environmental ones. Furthermore, the electrical conductivity of the nutrient solution can directly influence the nutrient content present in the substrate, especially when it is reused, thus interfering with absorption by plants. In this way, the present study aimed to determine the feasibility of reusing the substrate and determine the optimal concentration of the nutrient solution in tomato cultivation. The experiment was conducted in a greenhouse at the Department of Vegetable Crops and Aromatic Medicinal Plants, belonging to FCAV-UNESP. The 'Paronset' hybrid was cultivated in pots containing coconut husk fiber as substrate. The nutrient solution was evaluated at five concentrations, namely 25, 50, 100 (original solution), 150 and 200% of recommended solution, and the substrate at two usage levels (new and reused). Fertigation was performed by dripping with nutrient solution as recommended. The characteristics evaluated were: Production per plant, yield, number of fruits per plant, average fruit weight, soluble solids, and transverse and longitudinal fruit diameter. There was no interaction between the reuse of the substrate and nutrient solution concentration; moreover, there was no difference between the characteristics evaluated for all treatments. Under the conditions of this study, the reuse of the substrate is recommended, at least once, and the use of nutrient solution at a concentration of 25% of the original for the cultivation of 'Paronset' tomato hybrid.
Keywords: Coconut husk fiber; Fertigation; Greenhouse cultivation; Nutrient solution; Solanum lycopersicum